Patterns of practice in palliative radiotherapy for bone metastases in UK centres. Issue 2 (8th November 2018) - Khan, Nida; Green, David
Abstract: Background: There is abundant evidence of the comparative efficacy of single-fraction (SF) radiotherapy and multi-fraction (MF) radiotherapy when treating patients with bone metastases. Despite this, previous surveys have shown SF schedules to be underutilised. Aim: To determine current patterns of practice in patients with bone metastasis and to investigate the factors that influence practice. Method: An electronic audit was performed amongst 46 physicians, within 7 hospital trusts in the UK. The audit comprised of four hypothetical cases in which consultants and registrars chose which dose and fractionation they would recommend and their reasons for this recommendation. Results: SF radiotherapy was the most common radiotherapy schedule in hypothetical cases 1, 3 and 4. SF radiotherapy was recommended by 65% of respondents in case 1, 47% in case 2, 89% in case 3 and 46% in case 4. For case 2, 50% proposed MF radiotherapy. For case 4, 22% of respondents recommended Stereotactic Body Radiotherapy (SABR). The following deciding factors were cited as influencing choice of an SF schedule: prognosis, published evidence, performance status and spinal cord compression. Conclusion: The most common radiotherapy schedule selected was SF. However, there were inter-institution differences regarding the use of SF radiotherapy. Furthermore, the survey had shown that a third of respondents recommended an MF regime, despite evidence supporting the efficacy of an SF schedule.